Late Pleistocene hydroclimatic variabilities in arid north‐west China: geochemical evidence from Balikun Lake, eastern Tienshan, China. (9th March 2021) - Zhao, Yongtao; An, Cheng‐Bang; Zhou, Aifeng; Zhang, Xiaonan; Zhao, Jiaju; Dong, Weimiao; Miao, Yunfa
ABSTRACT: Reconstructing the environmental and hydrological response to millennial‐scale fluctuations of climate‐sensitive areas of mid‐latitudes is crucial to understanding the Late Pleistocene climate in terrestrial inland regions. We use sedimentological and geochemical proxies (e.g. lithology, gain size, loss‐on‐ignition, soluble salts, X‐ray fluorescence elements) from Balikun Lake in the eastern Tienshan Mountains, to elucidate variations in sedimentation, water chemistry and watershed weathering intensity of the Late Pleistocene interval (~20−60 ka). The record documents high‐frequency oscillations and alternating hydrological patterns on (multi‐) millennial timescales. Balikun Lake changes from nearly fresh to brackish and finally to hypersaline conditions during MIS3. The warm and wet climate during the early MIS3 facilitated regional vegetation and bioproductivity. Halite sedimentation took place from the middle to late MIS3, indicating a gradual drying trend. This reduced the lake area and vegetation cover, as well as weakened the chemical weathering rates of the watershed. These new interpretations challenge the idea of climate amelioration with the highest lake level and wettest conditions prevailing in the arid areas of north‐west China during the late MIS3, indicating a possible westerlies‐dominated Late Pleistocene climate in these areas. The evolution of the palaeohydrological regime and climate change in the Balikun Basin correlated well with the millennial‐scale high‐latitude Atlantic climate superimposed on the Northern Hemisphere summer insolation. Highlights: Evidence is presented for a warm and wet climate in arid western China during the early MIS3. The frequent occurrence of halite lithofacies in lake sediments indicates a gradual drying period from the middle to late MIS3. Evolution of the climate and paleohydrological regime in Balikun Basin follows millennial‐scale high‐latitude Atlantic climate cycles, superimposed on a climate that was largely driven by Northern Hemisphere summer insolation.